(3GdMLR Ydi GdSajfI (B/s - (3JQc, eMeO YHO GdaJGMs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2005)
(3GdMLR GdJMaVj Ydi GdSajfI, GdMLR GdJfajOj Ydi GdSajfIs
(3GdeQGLY U(B.152s
Keywords: (3GdbGfhf GdHMQjs; (3MLR GdeeJdcGJs